2020
DOI: 10.1002/ddr.21719
|View full text |Cite
|
Sign up to set email alerts
|

Curcumol improves cisplatin sensitivity of human gastric cancer cells through inhibiting PI3K/AKT pathway

Abstract: Background: Curcumol was presented to unleash antitumor effects in a variety of cancers, including gastric cancer. However, the relevance between curcumol and cisplatin resistance in gastric cancer still remains unclear. Therefore, the current research was performed to survey the role of curcumol in cisplatin sensitivity in gastric cancer. Methods: First, BGC-823 and BGC-823/DDP cells were incubated with cisplatin for 48 hr and 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…( Lei et al, 2019 ). Multiple studies have shown that curcumin can inhibit cell proliferation and migration in numerous proliferative diseases ( Hashem et al, 2020 ; Huang et al, 2020 ; Li et al, 2020 ). In summary, we chose tanshinone IIA and curcumol to preliminarily establish quality control ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…( Lei et al, 2019 ). Multiple studies have shown that curcumin can inhibit cell proliferation and migration in numerous proliferative diseases ( Hashem et al, 2020 ; Huang et al, 2020 ; Li et al, 2020 ). In summary, we chose tanshinone IIA and curcumol to preliminarily establish quality control ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that Curcumol can affect cell membrane potential by killing tumor cells, inducing apoptosis and differentiation of tumor cells [ 8 , 9 ]. Curcumol plays an anti-tumor role by inhibiting tumor nuclear metabolism, angiogenesis and anti-mutation [ 10 ]. It can inhibit the proliferation of cervical cancer, ovarian cancer, gastric cancer and nasopharyngeal cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the long-term use of Chinese traditional herbal medicines in treating malignant diseases [ 6 , 7 ]. The active ingredients extracted from natural plants have anti-GC actions and can slow down GC progression [ 8 , 9 ]. Amarogentin (AG), first reported to exert anticarcinogenic action against cutaneous carcinoma via inducing cancer cell apoptosis, is the main active component isolated from Swertiamarin, which has been shown to promote liver cancer cell apoptosis and play an anti-liver cancer part [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%